THE USE OF ENGLISH SONGS TO IMPROVE STUDENTS’ SPEAKING ABILITY - Sri Wahyuni; Hijjatul Qamariah; MulyadiSyahputra (Getsempena English Education Journal, 2018)
This study is to implement English songs in teaching speaking for English Department students at STKIP Bina BangsaGetsempena Banda Aceh. This research was quasi-experimental study. The aim of the study was to find out students' improvement in speaking ability by using English songs. The population of this study was the whole students of English Department of STKIP Bina BangsaGetsempena Banda Aceh in academic year 2015/2016. The sample is the second-semester students of English Department that consisted of 35 students. The data needed are recorded by testing students speaking test. The data were analyzed by using t-test. The result of the study is shown that the t-score was 7,25 the critical value of the t-score for the degree of freedom is 34 at the level of significance 0,05. The result showed that the calculation of the score is 7,25, it is higher than t-table 2,14, thus the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted which means that the use of English songs can improve students’ speaking ability.